1997
DOI: 10.1103/physrevlett.79.269
|View full text |Cite
|
Sign up to set email alerts
|

Type II Band Alignment inSi1xGex/Si(001)

Abstract: We present experimental verification of type II band alignment in a coherently strained Si 0.7 Ge 0.3 ͞Si͑001͒ quantum well by studying photoluminescence energy shifts under external strains. A recent determination of type I band alignment from a similar experiment is shown to result from band-bending effects due to high excitation. In high quality samples, the type II luminescence can be observed in the absence of external stress by using extremely low excitation. The type II luminescence differs from the wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(59 citation statements)
references
References 23 publications
4
54
0
1
Order By: Relevance
“…37 This was done due to the dearth of theoretical and experimental data for a-Sn. More recently, 40 imply E v,av (Si) ¼ À0.800 eV, and subsequent capacitancevoltage measurements at Si/Ge 1-x Si x interfaces are also in very good agreement with this value. 34 These results provide strong support for Li's theoretical results.…”
Section: Discussionsupporting
confidence: 70%
“…37 This was done due to the dearth of theoretical and experimental data for a-Sn. More recently, 40 imply E v,av (Si) ¼ À0.800 eV, and subsequent capacitancevoltage measurements at Si/Ge 1-x Si x interfaces are also in very good agreement with this value. 34 These results provide strong support for Li's theoretical results.…”
Section: Discussionsupporting
confidence: 70%
“…For example, even when the excitation power density increases from 1 to 4 W/cm 2 , the blueshift was as large as ϳ3.6 meV, in a 3-nmtype-II Ge 0.3 Si 0.7 /Si quantum well. 12 This NP dot PL peak blueshift ͑1.5 meV͒ of sample B is similar to the blueshift of the GeSi wetting layer, whose band alignment is type I, 4 so, the band alignment of sample B could be reasonably explained by a type-I band alignment and the blueshift is due to the band filling effect, 11 which is due to the finite density of states of the GeSi dots layer. The power dependence of the integrated PL intensities of the dots as shown in Fig.…”
mentioning
confidence: 68%
“…The power-dependent PL measurements were widely used to study the band alignment of the GeSi quantum dots, [2][3][4] SiGe/Si quantum well, 11,12 and III-V heterostructures. 13 In the type-II band alignment quantum structure, a band bending occurs at the interfaces due to the Hartree potential, as seen in the insets of Fig.…”
mentioning
confidence: 99%
“…It has also been found that, compared to two-dimensional (2D) Si/SiGe NSs, the PL and EL quantum efficiency in 3D Si/SiGe NSs is higher (up to 1%), especially for T > 50 K (Cerdeira et al, 1972;Apetz et al, 1995;Schittenhelm et al, 1995;Schmidt et al, 1999b). Despite many successful demonstrations of PL and EL in the spectral range of 1.3-1.6 μm, which is important for optical fiber communications, the proposed further development of 3D Si/SiGe-based light emitters was discouraged by several studies, indicating a type II energy band alignment at Si/SiGe heterointerfaces (Van de Walle and Martin, 1986;Thewalt et al, 1997;Schittenhelm et al, 1998;El Kurdi et al, 2006), where the spatial separation of electrons (located in Si) and holes (localized in SiGe) (see 1) was thought to make carrier radiative recombination very inefficient. Later, it was also shown that 3D Si/SiGe NSs exhibit an extremely long (of the order of 10 −2 s) luminescence lifetime (Kamenev et al, 2005), which is of the order of a million times longer than in III-V semiconductors and their NSs.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…So far, intense luminescence has been observed only at low temperatures in Si1−xGex in single and multiple QWs for x ≤ 0.2 [see Robbins et al (1992)]. There have been several studies of the energy band alignment (i.e., to determine whether it is type I or type II; see Figure 1) in these NSs, but no final conclusions have yet been reached (Houghton et al, 1995;Thewalt et al, 1997;Shiraki and Sakai, 2005). Si and Ge interdiffusion during the growth of Si/Si1−xGex QWs broadens the heterointerfaces, but this interdiffusion can be reduced by using moderately low growth temperatures (less than 550°C).…”
Section: Quantum Wellsmentioning
confidence: 99%